The Effect of Minimum Wages and Tax Revenues on Poverty in Indonesia - Tamaria Sidebang; Vivi Safira; Mentari Rezeki Ramadhani; M. Abdan Syakura; Azman (International Journal For Advanced Research, 2024)
This research aims to determine the effect of minimum wages and tax revenues on poverty in Indonesia. This research uses quantitative research which is centered on testing theory through measuring research variables based on numbers and analyzing data using statistical methods. This research data uses secondary data taken from the Central Statistics Agency in the form of data on Minimum Wages, Tax Revenues and Poverty in Indonesia. The results of the research show that the minimum wage has a significant negative effect on poverty, with every 1% increase in the minimum wage reducing poverty by 12.26378 %. Meanwhile, tax revenue has a significant positive influence on poverty, with every 1% increase in tax revenue increasing poverty by 19.89796%. These results show that minimum wage and tax revenue policies have an important role in reducing poverty in Indonesia.